Who uses mobile apps to meet strangers: The roles of core traits and surface characteristics. Issue 4 (2nd October 2017) - Zhang, Lixuan; Pentina, Iryna; Fox Kirk, Wendy
ABSTRACT: Digital space continues to be a popular venue for meeting new people. However, little is known about who uses mobile context-aware social networking apps to initiate new relationships. This study investigates the roles of individual core traits and surface characteristics in the adoption of social discovery features on WeChat, a mobile social networking app in China. Analysis of survey data collected from 213 WeChat users finds the core traits of agreeableness and neuroticism to be negatively related to the use of these social discovery features. The surface characteristic of sensation seeking is positively related to the use of social discovery features, while the surface characteristic of loneliness is not. Based on the findings, directions for future research and implications for app developers and marketers are suggested.